Teaching 6-12 math intervention : a practical framework to engage students who struggle - Tapper, Juliana (New York : Routledge, 2025)
"This practical resource offers a classroom-tested framework for secondary math teachers to support students who struggle. Teachers will explore an often-overlooked piece of the math achievement puzzle: the gatekeeping cycles of mathematics and the importance of teachers own expectations of students. The immediately applicable strategies in this book, developed through the author's work as a math intervention teacher, intervention specialist, and instructional coach, will give teachers the tools to help students overcome math anxiety, retention struggles, and even apathy. Beginning with a deep dive into the gatekeeping cycles to help teachers better understand their students who struggle, the book then walks teachers through the five-part B.R.E.A.K. it (TM) Math Intervention Framework: Build Community, Routines to Boost Confidence, Engage Every Student, Advance Your Expectations, Know Students' Level of Understanding. Educational research, personal anecdotes from the author's own classroom, and examples from case study teachers are woven into each chapter, leading to clear action items, planning strategies, and best practices that are accessible enough to accommodate all grade levels and schedules. The framework and activities in this book enable teachers to help students overcome math anxiety, create a safe math environment for 6-12 students, and ultimately increase achievement with effective research-based suggestions for working with students who struggle. Find additional resources at www.gatebreakerbook.com"
Includes references.
Keywords: Mathematics -- Study and teaching (Middle school).; Mathematics -- Study and teaching (Secondary).; Mathematical readiness